Environmental liability investigation in the area of the landfill of Hidrolândia, Go - Barros, Rosana Gonçalves; Dias, Pâmela Pereira; Araújo, Vanessa Kelly Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The improper disposal of solid waste has resulted in a scenario of numerous environmental damage such as soil contamination, surface and groundwater through the leachate. This study aimed to evaluate the chemical characteristics of the soil and leached from the landfill Hidrolândia, GO, in order to verify possible trends contamination of the area by heavy metals. The following surveys were conducted: location of the area and soil sampling points for assessment of physicochemical parameters and the presence of heavy metals and leachate sampling for analysis of heavy metals. The results were compared with the values guiding of Environmental Company of São Paulo (CETESB). Cadmium metals were detected, lead, copper, chromium, iron, mercury, nickel and zinc, where they had values below the limits established by CETESB. In the soil sample the iron element was detected with content of 311.41 mg l-1. The leachate analysis, only the iron was detected with a concentration of 33.00 mg L-1. Despite the great diversity and volatility of the waste deposited, there is insufficient evidence to prove the soil contamination in the study area by heavy metals analyzed.